Brain MRI Findings in Severe COVID-19: Case Report of Two Cases - Regmi, Pradeep R; Amatya, Isha; Kayastha, Prakash (Journal of Institute of Medicine Nepal, 2021)
Most of the imaging spectrums of COVID-19 are evolving day by day. Every other day, we get to know the imaging peculiarities in this novel disease. Apart from the chest involvement, neurological manifestations are well recognized in COVID-19 infection. The neurological manifestations are infarcts (ischemic or hemorrhagic), acute demyelination, acute necrotizing encephalomyelitis, micro-haemorrhages, acute demyelinating encephalomyelitis, leukoencephalopathy, global hypoxic injury, cranial nerve enhancement, cytotoxic lesions of the corpus callosum, olfactory bulb involvement and Guillain Barre Syndrome. Though the imaging findings in COVID-19 are non-specific and may not be diagnostic, proper correlation with the history and clinical spectrums can suggest the changes related to COVID-19. We have reported two severe COVID-19 cases that illustrate various neuroimaging manifestations.